Scintillations of Multiwavelength Gaussian, Cos, Cosh and Annular Gaussian Beams - Eyyuboglu, Halil T. (Springer Heidelberg, 2012)
We provide the scintillation formulation for a multiwavelength source. Within this context, the scintillation aspects of Gaussian, cos, cosh and annular Gaussian beams are investigated. For all situations examined, it is found that for a source comprising many wavelengths, there will be less scintillations as compared to a single wavelength source of the lowest wavelength and but the reverse will be true if the comparison is with respect to the single wavelength source of the highest wavelength. The same is observed at all propagation distances, source sizes, on-axis and off-axis positions considered. Additionally, it is seen that the scintillation characteristics of multiwavelength sources will follow similar trends of single wavelength sources. The analysis is based on the Rytov approximation, therefore our results are valid for conditions of weak atmospheric turbulence.
Scintillations of multiwavelength Gaussian, cos, cosh and annular Gaussian beams